Good urbanism : six steps to creating prosperous places - Ellin, Nan (Metropolitan Planning + Design, 2013)
We all have a natural nesting instinct-we know what makes a good place. And a consensus has developed among urban planners and designers about the essential components of healthy, prosperous communities. So why aren't these ideals being put into practice? In Good Urbanism, Nan Ellin identifies the obstacles to creating thriving environments, and presents a six-step process to overcome them: prospect, polish, propose, prototype, promote, present. She argues that we need to reach beyond conventional planning to cultivate good ideas and leverage the resources to realize them. Ellin illustrates the process with ten exemplary projects, from Envision Utah to Open Space Seattle. Each case study shows how to pair vision with practicality, drawing on our best natural instincts and new planning tools. For planners, urban designers, community developers, and students of these fields, Ellin's innovative approach offers an inspired, yet concrete path to building good places.